ANALISIS SIMRS PADA BAGIAN PENDAFTARAN PASIEN MENGGUNAKAN METODE PIECES DI RSKIA UMMI KHASANAH - Supriyanti, Supriyanti; Windarti, Syamsu; Muslim, Muhammad (Politeknik Kesehatan Kemenkes Malang, 2023)
Background: Hospitals need fast and accurate patient registration services because they are responsible for organizing health efforts. Utilization of information technology is the solution, namely a hospital management information system as a tool to support patient services that will. Ummi Khasanah Hospital has used a hospital management information system in providing services, but there are still problems complained of by registration officers. The strategy to reduce the risk of this problem is to analyze the PIECES method.Subjects and Method: The type of research used is descriptive qualitative. This research was conducted at RSKIA Ummi Khasanah with 3 registrars. Data collection techniques using interview techniques using interview guidelines and observation using an observation checklist.Results: The results of the study show that based on the performance aspect, the information system operate according to the needs of the registration officer even though several menus cannot be used. The general information aspect is quite accurate, the economic aspect has not produced economic value because the hospital management information system cannot be integrated with other information systems. The control aspect has been running well, namely, there are restrictions on access and there is system security in the form of the availability of passwords and usernames, the efficiency and service aspect is appropriate because the hospital management information system can be used easily and speeds up the service process.Conclusion: Based on the results of this analysis, the hospital management information system has been used well in the patient registration section but several menus and features cannot be used optimally.